Il ruolo dell’abitudine nella costruzione dell’identità morale in The Mill on the Floss e Middlemarch di George Eliot (Itinera, 2024)
What is the boundary between unconscious habits and conscious actions? This is the question that drives all of George Eliot’s poetics centered on the importance of habit in the construction of her characters’ moral identity. The aim of this article is to analyze the author’s answers in this regard through two of her formidable novels: The Mill on the Floss and Middlemarch. In the first work, recovering the image, of philosophical- psychological origin, of the mind as a channel and making use of the analogies between animal and human behavior, Eliot proposes imaginative experience as a means of developing new cognitive capacities. But it is in Middlemarch that Eliot adds a further piece: unhinging the misogynistic prejudices attached to the concept of habit typical of the strongly patriarchal culture of the Victorian age. Pointing her satirical pen at the habits of her characters, Eliot invites readers to a critical attitude toward their own habits. Reading thus becomes an opportunity to reflect on our pervasive habits and achieve that gradual change towards the construction of a more mature and conscious moral identity.
Keywords: George Eliot, habit, moral identity, emancipation.